Government finance : economics of the public sector - Due, John F. (Homewood, Illinois R. D. Irwin, 1968)
Decision making for governmental activities and expenditures, integrating the work of political science, administrative theory and economics.
Includes bibliographical references, index.
sju 22/01/2019
Loans
Keywords: Government finance; Finance, Public; Public sector